Activated Carbon Coating Films from Renewable Resources: Advancing Eco-Friendly Food Packaging - Redzuan Mohammad Suffian James; H'ng Paik San; Norwahyuni Mohd Yusof; Seng Hua Lee (BioResources)
As sustainability and food safety continue to gain more attention, the demand for environmentally friendly packaging materials has increased significantly. This review emphasizes the transformative potential of activated carbon derived from renewable sources in addressing critical challenges in food packaging. Activated carbon is recognized for its outstanding adsorption capacity, large surface area, and porous structure, which enable it to capture gases such as oxygen, moisture, and ethylene, all of which contribute to food deterioration. In addition to these properties, activated carbon exhibits antimicrobial activity and can facilitate the release of nanoparticles, thereby enhancing food safety through the inhibition of microbial growth. Its multifunctional characteristics make it suitable for various uses, including prolonging shelf life and maintaining the sensory attributes of food products. The local production of activated carbon from agricultural residues supports circular economy practices by reducing reliance on fossil-based resources and minimizing environmental impact. This review highlights the important role of activated carbon in the development of sustainable and multifunctional food packaging technologies that support global initiatives aimed at reducing plastic waste and promoting green innovation.